Czynności zawodowe lekarzy w czasie stanu epidemii – problemy wybrane - Łątka-Płachta, Monika (Czasopismo Prawa Karnego i Nauk Penalnych, 2021)
The ongoing epidemic has changed the socially acceptable risk and, as a result, the rules of dealing with legal goods. However, the doctor’s criteria of priority cannot be arbitrary ones, i.e., the ones that violate achievements such as gender or racial equality. These criteria cannot include “buddy-buddy” rules, i.e., rules that allow for the acceleration of medical treatment due to the existing sympathy between the doctor and the patient. At the same time, heroism cannot be required of a doctor. This means that in a situation in which the rules of dealing with a legal good (including the rules of priority of duty) do not prescribe a specific action, a doctor may proceed to save a person dear to him, instead of a stranger. During an epidemic, when the speed of triage is of no small importance, such a possibility that someone who is not a professional would be involved in such assessment is most acceptable, especially in the face of a change in the rules of dealing with legal goods. However, the behavior of such a person cannot be evaluated on an equal footing with that of a professional, as they are not equally qualified.